PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI DAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada PT. Asuransi Jiwa Manulife Indonesia) - Denny Asmas; Anisah Anisah (Universitas Batanghari Jambi, 2015)
Goals to be achieved from this research was to determine the effect of budgetary participation on managerial performance, the effect of budgetary participation in improving managerial performance through organizational commitment, the effect of budgetary participation in improving managerial performance through job satisfaction, organizational commitment influence on managerial performance, job satisfaction influences on managerial performance partially, as well as to determine the effect of budgetary participation, organizational commitment and job satisfaction affect managerial performance in PT Asuransi Jiwa Manulife Indonesia in Simultaneous .This method of the research using a survey method by distributing questionnaires, whereas analysis methods of data analysis using multiple regression and statistical approaches to test validity and reliability, the classical assumptions and hypothesis testing. Methods of data collection using a questionnaire in instrumental research via e-mail by taking samples in accordance with the provisions or criteria established by the researcher or purposive sampling technique.The results of testing the hypothesis of this study concluded that budgetary participation and organizational commitment as a variable intervening, budget participation and job satisfaction as a variable intervening, organizational commitment and job satisfaction is a significant positive effect on managerial performance at Manulife Financial. In Simultaneous, budget participation, organizational commitment and satisfaction ja ker positive and significant effect on managerial performance at Manulife Financial uji_ as evidenced by the significant value of F is 0.000 <0.05. Keywords: Participation budget, organizational commitment, job satisfaction and managerial performance